PERBEDAAN HASIL BELAJAR MENGGAMBAR BUSANA DENGAN PENGGUNAAN MEDIA KOMIK DAN MEDIA GAMBAR DI SMK PGRI 1 SALATIGA - Rubiyati Rubiyati (KELUARGA: Jurnal Ilmiah Pendidikan Kesejahteraan Keluarga, 2015)
The objectives of this research are to know the students’ achievement for those who are taught by (1) picture media, (2) comic media, and (3) the different achievement in drawing dress between picture and comic media.  The type of the research is ex-post facto and sampling research. Data are collected by questionnaire and documentation. Data analysis techniques apply descriptive and comparative analysis. The result shows that the achievement in drawing dress by comic media  is categorized high by and picture media is fair. Based on the comparative exam, it shows that there is positive and significant difference between the achievement in drawing dress by comic and picture media. The use of picture and comic media in drawing dress give experience to the students.